Children With Autism Spectrum Disorder and Their Mothers Share Abnormal Expression of Selected Endogenous Retroviruses Families and Cytokines - Balestrieri, Emanuela; Cipriani, Chiara; Matteucci, Claudia; Benvenuto, Arianna; Coniglio, Antonella; Argaw-Denboba, Ayele; Toschi, Nicola; Bucci, Ilaria; Miele, Martino Tony; Grelli, Sandro; Curatolo, Paolo; Sinibaldi-Vallebona, Paola (Frontiers in Immunology, 2019)
The Autism Spectrum Disorder (ASD) is a heterogeneous group of neurodevelopmental disorders, clinically diagnosed since the lack of reliable biomarkers. Autism aetiology is probably attributable to the combination of genetic vulnerability and environmental factors, and recently, maternal immune activation has been linked to derailed neurodevelopment, resulting in ASD in the offspring. Human endogenous retroviruses (HERVs) are relics of ancestral infections, integrated in the human DNA. Given the HERV persistence in the genome, some of HERVs have been coopted for physiological functions during evolution, while their reactivation has been associated with several diseases, including cancer, autoimmune and neurological/psychiatric disorders. Particularly, due to their intrinsic responsiveness to external stimuli, HERVs can modulate the host immune response and in turn HERVs can be activated by the immune effectors. In previous works we demonstrated high expression of HERV-H in blood of autistic patients, closely related with the severity of the disease. Moreover, in a preclinical ASD model we proved changes of expression of several ERV families and cytokines from the intrauterine life to the adulthood and across generations via maternal lineage. Here we analyzed the expression of HEMO and of selected HERVs and cytokines in blood from ASD patients and their parents and corresponding healthy controls, to look for a common molecular trait within family members. ASD patients and their mothers share altered expression of HERV-H and HEMO and of cytokines such as TNF-α, IFN-γ, IL-10. The multivariate regression models showed a mother-child association by HEMO activity and demonstrated in children and mothers an association between HERV-H and HEMO expression and, only in mothers, between HEMO and TNF-α expression. Furthermore, high diagnostic performance for HERV-H and HEMO was found, suggesting their potential application for the identification of ASD children and their mothers. The present data support the involvement of HERVs in ASD and suggest HERVs and cytokines as ASD-associated traits. Since ASD is a heterogeneous group of neurodevelopmental disorders, a single determinant alone could be not enough to account for the complexity, and HERV/cytokines expression could be considered in a set of biomarkers, easily detectable in blood and potentially useful for an early diagnosis.